228 nm pulse duration dependence in the photodissociation of H2+. (31st October 2017) - Jia, Z M; Tang, W T
Abstract: We theoretically investigate the pulse duration dependence in the laser-induced dissociation of the molecular ion H 2 + . The simulation results show that the dissociation ratio can be split up into three regions with increasing duration of the external laser pulse, with a central wavelength of 228 nm, as a result of the electron capture of the vibrationally highly excited H 2 + . With the coupled equations of the 1 s σ g and 2 p σ u states one can find that the pulse duration dependence in the photodissociation of H 2 + is due to the different responses of the molecular dipole to the evolution time of the ultraviolet laser pulse.